(untitled) (El-Wahat Journal for Research and Studies, 2025)
This paper presents a comparative analysis of the emotiveness present in Turkish and English headlines sourced from Euronews, BBC, and AA channels. Emotiveness plays a crucial role in capturing readers’ attention and eliciting emotional responses. Understanding how emotive language is employed in headlines across different news channels in Turkish and English languages provides valuable insights into their cultural and linguistic dynamics. Using a corpus-based approach, this study examines a diverse range of headlines collected from Euronews, BBC, and AA channels. The analysis focuses on the linguistic devices, rhetorical strategies, and cultural references employed in the headlines to create emotive effects. It explores how these channels adapt their headline styles to engage their respective audiences and elicit desired emotional responses.The findings shed light on the ways in which these channels employ emotive language to inform, persuade, and engage their audiences. Keywords: Headline titles, Turkish headlines, English headlines, Emotiveness, Reader Response theory